Rahmah al-Yūnusiyah, Mu’assisah al-Ma‘had al-Dīnī li al-Banāt Bādānj Bānjānj—Sūmatrah al-Gharbiyyah - Rasyad, Aminuddin (Studia Islamika, 1997)
Rahmah al-Yunusiyah was born on December 29, 1900 and grew up in an Islamic family in Padang Panjang in West Sumatra. His father was a religious functionary of the local Isalmic court (qadi) while her gran father was a shaykh of the Nagshabandiyyah sufi order. Her oldest brother, Zainuddin Labai al-Yunusi (1890-1924) was one of the great Islamic reformers in Minangkabau. In 1915, he established the Diniyah school, the first modern Islamic school in Indonesia. In that school, Zainuddin, among other things implemented the classical learning system, co-education and modern sciences at a time when most Islamic school were stil preoccupied with traditional Islamic science.DOI: 10.15408/sdi.v4i2.782